The using of marketing elements to create customer awareness towards insurance: a study of Maktab Rendah Sains Mara (MRSM) teachers in Melaka / Maizatul Akmaliah Mat Zain - Mat Zain, Maizatul Akmaliah (Faculty of Business and Management, 2009)
This research exploring the customer awareness towards the importance of insurance, and how well insurer has been convincing its customers who serves as a protection and financial solution provider through elements of marketing or 4P’s namely; product, distribution, promotions and price. The objective of the study is to determine level of customer awareness towards Insurance. Besides, to identify factors those influence awareness of customer towards insurance. As well as to determine the most influence factors that increase customer awareness towards insurance. The study also uses to find the recommendations or solutions in order to increase customer awareness towards insurance. Method has been used to conduct this research is using primary and secondary data in getting the data needed. The study is using stratified sampling that take respondent from Maktab Rendah Sains Mara (MRSM) in Melaka to answer the questionnaire given to them.